2D Sequential Restoration and Basin Evolution of the Wichianburi Sub-basin, Phetchabun Basin, Central Thailand - Jitmahantakul, Sukonmeth; Phetheet, Jirapat; Kanjanapayont, Pitsanupong (Frontiers in Earth Science, 2020)
The Wichianburi Sub-basin is currently the only productive area in the southern part of the Phetchabun Basin, central Thailand. It is structurally dominated by NNW-SSE to NNE-SSW trending normal faults as a result of multistage rifting since the Late Oligocene. Half-graben and full-graben basin geometries can be observed from 2D regional seismic sections. In this study, structural restoration techniques were applied to validate the structural interpretation of the original hardcopy of the 2D seismic sections. Stratigraphic information is compiled from published papers and well reports. Our results revealed that most of the deformation was concentrated during the Late Oligocene. Main depocenters for the syn-rift sediments focused in the basin center along the west-dipping normal faults. These faults cut the prerift section and their orientations were possibly controlled by the Permo-Triassic fabrics that underlie the Phetchabun Basin. By measuring the length of the profiles before and after faulting, the restorations show that the extensions of the Wichianburi Subbasin decrease from 12.30% during the main rift phase (Late Oligocene to Early Miocene) to 2.53% during the second phase of rifting. Rifting only focused in the basin center with the development of NNW-SSE to N-S trending intrarift faults. Since the Middle Miocene, the Wichianburi Subbasin has developed under the tectonic phase of post-rift subsidence with interruption by intrusive activities.